2020
DOI: 10.3390/chemosensors9010004
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Carboxylate Sensors Based on Carbazole-Derived Acyclic and Macrocyclic Ionophores

Abstract: Solid-contact ion-selective electrodes with carbazole-derived ionophores were prepared. They were characterized as acetate sensors, but can be used to determine a number of carboxylates. The potentiometric response characteristics (slope, detection limit, selectivity, and pH sensitivity) of sensors prepared with different membrane compositions (ionophore, ionophore concentration, anion exchanger concentration, and plasticizer) were evaluated. The results show that for the macrocyclic ionophores, a larger cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…The second strategy relies on dissolving the receptor into the ISE membrane cocktail, thus embedding the ionophore into the electrode body. 6,7 Here, no specific functional group is necessary for immobilization. However, this introduces the possibility for the ionophore that it may leak into the analyte solution from the ISE membrane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The second strategy relies on dissolving the receptor into the ISE membrane cocktail, thus embedding the ionophore into the electrode body. 6,7 Here, no specific functional group is necessary for immobilization. However, this introduces the possibility for the ionophore that it may leak into the analyte solution from the ISE membrane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As can be concluded from the p K a values (in DMSO) of pyrrole (23.0), indole (20.9) and carbazole (19.9), 32 the acidity of the pyrrole ring can be increased not only by attaching electron-withdrawing groups but also by conjugation with the benzene ring. 33 The groups of Jurczak, 34 Sessler, 35 and Gale 36,37 and our group 38–40 have used the carbazole ring as an effective component of anion receptors. The carbazole ring is used not only because of its higher acidity but also for its rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that carbazole's rigid skeleton enables the introduction of various functionalities, which makes it an ideal moiety for the design of anion receptors. 34–40…”
Section: Introductionmentioning
confidence: 99%
“…Solid-contact materials based on conducting polymers (e.g., PEDOT-see Figure 1b, poly(aniline), poly(pyrrol), etc.) are conveniently made by electrodeposition-polymerization of the monomer on an electrode, such as glassy carbon (GC) [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. It has also been shown that some conducting polymers, polymerized in the presence of different anions, can behave as ISMs for cations or anions [79,85,86].…”
Section: Introductionmentioning
confidence: 99%